Protective Effect of Black Rice Extract Cream on Ultraviolet B-Induced Skin Hyperpigmentation in Mice - Maryanti, Maryanti; Putra, Agung; Subchan, Prasetyowati (Althea Medical Journal, 2025)
Background: Hyperpigmentation is a common sign of skin aging caused by prolonged ultraviolet B (UVB) exposure. Black rice (Oryza sativa L. var glutinosa), known for its high antioxidant content, has moisturizing and regenerative properties that may support skin health. This  study aimed to evaluate the effect of black rice extract cream on transforming growth factor beta (TGF-β) and tumor necrosis factor alpha (TNF-α) expression in a UVB-induced hyperpigmentation mouse model.Method: An in vivo experimental study with post test only control group design was conducted in 2024 at the Stem Cell and Cancer Research Laboratory, Semarang, Indonesia. Twenty-eight male C57BL/6 mice were randomly divided into four groups: healthy control (K1),  UVB-exposed negative control group (K2), UVB-exposed group treated with  7.5% (K3) and 15 % (K4) black rice extract cream  for14 days. On day 15, TGF-β and TNF-α expression levels were analyzed using the RTq-PCR,  normalized to GAPDH. Data were analyzed using One-way ANOVA followed by post-hoc testing.Results: TGF-β gene expression was the highest in K4 (1.87±0.23), followed by K3 (1.52±0.42l) which was statistically significant different between groups (p=000); whereas TNF-α gene expression was the lowest in K4 (1.92±1.02) compared with K3 (5.40±2.28), and the difference between groups was also statistically significant (p=000).  Conclusion: Black rice extract cream increase TGF-β expression and reduces TNF-α expression in UVB-induced hyperpigmentation. These findings suggests its potential as a natural topical agent to mitigate UVB-induced skin damage and premature aging.